The complex existence of γδ T cells following transplantation: the good, the bad and the simply confusing - Sullivan, Lucy C (Clin Transl Immunology, 2019)
Gamma delta (γδ) T cells are a highly heterogeneous population of lymphocytes that exhibit innate and adaptive immune properties. Despite comprising the majority of residing lymphocytes in many organs, the role of γδ T cells in transplantation outcomes is under‐researched. γδ T cells can recognise a diverse array of ligands and exert disparate effector functions. As such, they may potentially contribute to both allograft acceptance and rejection, as well as impacting on infection and post‐transplant malignancy. Here, we review the current literature on the role and function of γδ T cells following solid organ and hematopoietic stem cell transplantation.